استخدام التكنولوجيا الحديثة في تطوير الحقل الإعلامي الأكاديمي و تناسق مخرجاته مع متطلبات سوق العمل دراسة ميدانية على أساتذة الإعلام والاتصال بالجزائر - بوسنان, رقية (جامعة الوادي - University of Eloued, 2022)
هدفت الورقة إلى مناقشة استخدام التكنولوجيا الحديثة في تطوير الحقل الإعلامي الأكاديمي وتناسق مخرجاته مع متطلبات سوق العمل، من وجهة نظر الأكاديميين المتخصصين في مجال علوم الإعلام والاتصال، وتوصلت الدراسة إلى نتائج هامة، ومنها أن التكنولوجيا الحديثة أساسية في تعليم الطلبة وتغيير نمط هذا التعليم للأفضل، بالرغم من النقص الفادح التي تعانيه الجامعة الجزائرية من توفير هذه التكنولوجيا. The paper aimed to discuss the use of modern technology in developing the academic media field and the consistency of outputs with the requirements of the labor market, from the viewpoint of academics specializing in the field of media and communication sciences. the study reached Important results, which include that the basic modern techniques in student education and changing the pattern of this education for the best, despite the severe shortage experienced by the Algerian University in providing these technologies.
The use of modern technology in the development of the academic media field and the consistency of its outputs with the requirements of the labor market A field study of media and communication professors in Algeria
مقال
Keywords: التكنولوجيا، الحقل الإعلامي، المخرجات، سوق العمل.; technology, media field, outputs, labor market